2013
DOI: 10.1111/dsji.12003
|View full text |Cite
|
Sign up to set email alerts
|

A Preliminary Study of Grade Forecasting by Students

Abstract: This experiment enabled undergraduate business students to better assess their progress in a course by quantitatively forecasting their own end-of-course grades. This innovation provided them with predictive feedback in addition to the outcome feedback they were already receiving. A total of 144 students forecast their grades using an instructorprepared spreadsheet, and then responded to a brief survey. Of these participants, 29% said the forecast grades were lower than expected, while 6% said they were higher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
1
2
0
Order By: Relevance
“…For both parameters, the differences between participants and nonparticipants are statistically significant ( p = .000). As with previous research (e.g., Armstrong, 2013; Westerman, Perez‐Batres, Coffey, & Pouder, 2011), students with stronger academic performance were more likely to participate.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…For both parameters, the differences between participants and nonparticipants are statistically significant ( p = .000). As with previous research (e.g., Armstrong, 2013; Westerman, Perez‐Batres, Coffey, & Pouder, 2011), students with stronger academic performance were more likely to participate.…”
Section: Resultssupporting
confidence: 80%
“…Our study also extends Armstrong and MacKenzie (2017) by considering how students’ academic abilities might moderate the way they respond to grade gaps. Previous research has shown that students with weaker academic performance tend to have worse predictive accuracy and are more prone to overestimating their grades (Armstrong, 2013; Kruger & Dunning, 1999). Since students with weaker ability are more prone to have grade gaps (Armstrong & MacKenzie, 2017), it is plausible they will also have more problems in responding effectively to such gaps.…”
Section: Introductionmentioning
confidence: 99%
“…This result is in line withPark and Santos-Pinto (2010) where players' ratings were used as a measure of their skill.36 Effectiveness of the joint action of self-chosen goals and real monetary incentives in higher education is shown in Herranz-Zarzoso and Sabater-Grande (2018).37 Examples areKruger and Dunning (1999),Grimes (2002),Falk and Knell (2004),Svanum and Bigatti (2006),Andrews et al (2007),Nowell and Alston (2007),Burns (2007),Jensen and Moore (2008),Khachikian et al (2011),Armstrong (2013), Tsigaris (2013, 2015),Sackett et al (2014)Query,Serra and DeMarree (2016),Sturges et al (2016), Foster et al (2017 andClark et al (2020).…”
mentioning
confidence: 58%